Interventions of tertiary education trust fund (Tetfund) and lecturers’ productivity in Kogi State Colleges Of Education, Nigeria - Omosidi, Abdulrahman; Atolagbe, Adedapo Adetiba; Johnson, Bola (Kuras Institute, 2023)
The study examined the Interventions of Tertiary Education Trust Fund(TETFUND) and lecturers’ productivity in government owned Colleges of Education in Kogi State, Nigeria. The research design adopted for this study was descriptive study. The population of this study were lecturers and the management staff in the selected Colleges of Education in Kogi State. The instruments used include “Tertiary Education Trust Fund Intervention Allocation checklist” (TETFIAC), “Tertiary Education Trust Fund Intervention Assessment questionnaire “(TETFIAQ) and Lecturers’ Productivity Assessment Questionnaire” (LPAQ). The reliability values of the instruments were 0.80 and 0.75 for TETFIAD and LPAQ respectively. Descriptive statistics such as mean and standard deviations were used to analysis the seven research questions raised in the study. It was revealed from the findings that TETFund has done considerably well by having moderate interventions on staff training and development, research and academic growth , instructional facilities, library development and physical infrastructure and these levels of interventions has significant impacts on the level of lecturers’ productivity in government owned Colleges of Education in Kogi State, Nigeria. The study recommended among others that the management of government owned Colleges of education in Kogi State to intensify efforts on meeting all necessary requirements for accessing and releasing of all approved funds form TETFund.